EARTHEN ARCHITECTURE: HELPING THE VICTIMS OF THE 2007 FLOOD IN BANDIAGARA, MALI - Cissé, Lassana; Joffroy, Thierry (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
On 4 July 2007, the river crossing the city of Bandiagara overlowed due to unusually heavy rains. Within few minutes, 194 families (nearly 1,500 people), witnessed the devastation of all or part of their homes and means of subsistence. At that time, the Cultural Mission of Bandiagara and CRAterre were collaborating in the framework of the project “Renforcement des capacités locales pour une meilleure contribution du secteur de la construction au développement durable du pays dogon” (Reinforcement of local capacities for a better contribution of the construction sector to the sustainable development of Dogon country) inanced by the European Union; they called upon institutions to enable them to include, as part of their activities, a contribution to the reconstruction of basic housing structures. The German organization “Misereor” and the Abbé Pierre Foundation, based in France, responded positively by funding the reconstruction of 20 houses for sheltering the most affected families. The project was carried out in collaboration with the local Catholic Parish (Caritas), the municipality, the Flood Victims’ Association, district chiefs, and the prefecture. A Committee was established to carefully select the 20 recipient families, which would commit to collecting materials from their affected properties and participate in the construction-training activities implemented. This reconstruction project beneited from the results of an inventory of the building cultures in Dogon country that included the study of land plots, building typologies and construction techniques. On the basis of these principles, 20 basic houses were designed and built, each with a different plan, deined by the types of materials recovered, the priorities identiied by the families and the possibilities for future extensions. The reconstruction process was an opportunity to demonstrate and train workers to master innovative lood-proof building techniques and combine them with traditional practices.